Manusia dalam Tinjauan Falsafah Pendidikan Hasan Langgulung - Badruzaman, Badruzaman (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
Hasan Langgulung is one of the Southeast Asian Muslim thinkers who devoted much attention to the Islamization of Science, especially in the field of education and psychology. He issued to combine modern western thoughts with regard to Islam. Hasan Langgulung died on August 2, 2008 at the age of 74 years. During the time, he has made many articles and books in various languages, philosophies and Islamic studies. Like English, Arabic, Indonesian and Malay, even some of them read back to other languages like the Philippines.The journal is a library research. Data writing techniques emphasize text analysis and study, library research is done by collecting literature related to research material, whether in the form of books, magazines, articles or opinions and the primary book in this research is the book of Man and Education: A Psychological Analysis and Education, Principles of Islamic Education, Islamic Education and Civilization, Creativity and Islamic Education: Analysis of Psychology and Philosophy, Islamic Education Faces the 21st Century, Some Thoughts on Islamic Education by Hasan Langgulung. According to Hasan Langgulung; humans are essentially created to carry out the duty of service to the creator (‘abdullah) and his duty as the caliph of Allah (Khal?fatullah) on the face of the earth. The purpose in humans with the religion of Islam is: (1) so that humans carry out their functions as caliphs, and (2) so that humans always serve God.